The effect of attachment types and implant level on the stress distribution in a mandibular overdenture: a 3D Finite Element Analysis - Aalaei, Shima; Abedi, Paria; Niknami, Sahar; Taghavi , Farnoosh; Taghavi Damghani, Farnaz (Brazilian Dental Science, 2022)
Objective: The objective of this study was to evaluate the stress distribution in bone-surrounding implants placed in different levels in a mandibular overdenture. Material and Methods: A Computerized Tomography (CT) scan of an edentulous mandible was used to generate the models. Two implants with an internal connection were placed perpendicular to the occlusal plane in the Canine sites of the mandible. The implant in the left side was placed 1mm higher than the other side. Dolder bar and ball attachments were designed. Loading was performed by clenching the teeth with reconstruction of the muscles. In the anterior loading condition, force was applied to the central incisors and in the posterior loading conditions, it was applied to the molars and premolars. Then the Maximum Principal Stresses in the peri implant bone was evaluated with finite element analysis. Results: In both models, the highest stress values were recorded in the cortical bone surrounding the higher implant except in the ball model with unilateral load application on the right side (64.7 MPa). In almost all loading conditions the stress value differences in models with bar and ball attachments were low. Only in the anterior loading condition, the stress magnitude was higher in two implants of the ball model (60.5 MPa in the left side and 21 MPa in the right side) compared to the bar model (54.5 MPa in the left side and 17.5 MPa in the right side). Conclusion: The stress concentration did not affected considerably by the attachment system. High stress values were found adjacent the implant with a higher level. To reduce the amount of stress, bilateral balance occlusion should be considered. KEYWORDS Stress; Finite element analysis; Overdenture; Dental implants.